Utilization of antenatal care services and correlates of anaemia among pregnant women attending a tertiary care hospital in Assam, India - Baruah, Anuja; Boruah, Beeva (International Journal Of Community Medicine And Public Health, 2017)
Background: Anaemia is one of the most commonly encountered medical disorders during pregnancy. As per NFHS-3 Assam 72% pregnant women are anaemic. Besides many adverse effects on mother and foetus, anaemia contributes significantly high maternal mortality. Early Antenatal booking and regular follow-up provides opportunities for delivering timely and essential interventions to the pregnant women. This study aims to explore the socio-demographic factors influencing the pattern of antenatal care services utilization and also to estimate the burden of anaemia in Assam. Methods: A cross-sectional hospital based study was carried out for three months, from November 2011 to February 2012 in Jorhat Medical College Hospital using a predesigned, pretested proforma. A total of 1845 women admitted in the postnatal ward were studied. Results: Only 9.51% were illiterate, 64.89% were primigravidae, 70.09% had no previous living issues. All were registered for ANC, of whom 57.62% were registered in the first trimester; 57.98% had adequate ANC; 65.97% received full course of IFA tablets. Adequate ANCs were availed in the younger age groups, the primigravidae and up to two living children. A total of 61.69% pregnant women were found to be anaemic; 46.80% mildly, 12.85% moderately and 2.03% severely anaemic. Most participants in 20-25 years age group (63.7%) and lower socio-economic class (62.63%) were found to be anaemic. Participants who registered for ANC after 12th week (83.4%), attended inadequate number of ANCs (70.06%), and failed to take IFA tablets (60%) were found anaemic. Conclusions: A total of 61.69% pregnant women were found to be anaemic. Early detection and effective management of anaemia in pregnancy can contribute substantially to reduction in maternal mortality.